2014
DOI: 10.1515/mammalia-2013-0032
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary investigation into the endoparasite load of the European hedgehog (Erinaceus europaeus) in Ireland

Abstract: Access to the full text of the published version may require a subscription. Abstract: The European hedgehog is strictly protected in the Republic of Ireland but has been little studied. Carcasses, such as road kill casualties, can provide valuable information on population demographics, parasite load and general body condition. This study aimed to examine the species of endoparasites present in hedgehogs, their prevalence and intensities and whether differences occurred depending on the age and sex of the hed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 15 publications
(28 reference statements)
4
27
1
Order By: Relevance
“…[21] – [24] ). These are complimented by several more recent studies [16] , [25] [27] . In contrast to this, only limited information is available on the parasites of EC (e.g.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…[21] – [24] ). These are complimented by several more recent studies [16] , [25] [27] . In contrast to this, only limited information is available on the parasites of EC (e.g.…”
Section: Discussionsupporting
confidence: 59%
“…Studies from southern Europe also found those parasites in EE ( [40] Iberian Peninsula, Spain, n = 125, P. clausa : 6.4%, N. major : 0.8%; [50] Sicily, Italy, n = 39, N. major : 69.2%; [51] Sicily, Sardinia, Emilia-Romagna, Italy, n = 34–53, P. clausa : 0–3%, N. major : 0–69%). However, more recent studies did not find either of these species in EE from Central Europe and the UK [16] , [25] , [27] . Both parasite species are transmitted via the ingestion of infected insect intermediate hosts [52] .…”
Section: Discussionmentioning
confidence: 97%
“…Jones & Norbury 2011), and our study suggests that hedgehogs have a diverse diet in urban forest fragments. As in other studies, hedgehogs are likely to prey switch seasonally, and in different habitats, throughout the year whereby they exploit one type of prey based on availability, before moving on to the next (Yalden 1976;Wroot 1984;Hendra 1999;Haigh 2011). Seasonal differences could not be assessed in this study as hedgehogs were only collected in spring and summer.…”
Section: Impactmentioning
confidence: 64%
“…The activity of I. hexagonus is closely linked to the density and behaviour of its primary host, the European hedgehog ( Erinaceus europaeus ) [ 31 ]. I. hexagonus is more prevalent earlier in the year than I. ricinus [ 31 , 32 ], coinciding with the emergence of hedgehogs from hibernation [ 33 ], and possibly explaining the earlier peak of tick activity we identified in cats. The second autumnal peak could represent interaction between cats and hedgehogs at a time when hedgehogs are preparing for hibernation and juveniles are gaining independence, leading to greater hedgehog numbers being seen [ 33 ], all at a time when I. hexagonus is also at great abundance on the hedgehogs themselves [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%